An original phylogenetic approach identified mitochondrial haplogroup T1a1 as inversely associated with breast cancer risk in BRCA2 mutation carriers. Issue 1 (December 2015) - Blein, Sophie; Bardel, Claire; Danjean, Vincent; McGuffog, Lesley; Healey, Sue; Barrowdale, Daniel; Lee, Andrew; Dennis, Joe; Kuchenbaecker, Karoline; Soucy, Penny; Terry, Mary; Chung, Wendy; et al.
Abstract Introduction Individuals carrying pathogenic mutations in theBRCA1 andBRCA2 genes have a high lifetime risk of breast cancer.BRCA1 andBRCA2 are involved in DNA double-strand break repair, DNA alterations that can be caused by exposure to reactive oxygen species, a main source of which are mitochondria. Mitochondrial genome variations affect electron transport chain efficiency and reactive oxygen species production. Individuals with different mitochondrial haplogroups differ in their metabolism and sensitivity to oxidative stress. Variability in mitochondrial genetic background can alter reactive oxygen species production, leading to cancer risk. In the present study, we tested the hypothesis that mitochondrial haplogroups modify breast cancer risk inBRCA1/2 mutation carriers. Methods We genotyped 22, 214 (11, 421 affected, 10, 793 unaffected) mutation carriers belonging to the Consortium of Investigators of Modifiers ofBRCA1/2 for 129 mitochondrial polymorphisms using the iCOGS array. Haplogroup inference and association detection were performed using a phylogenetic approach. ALTree was applied to explore the reference mitochondrial evolutionary tree and detect subclades enriched in affected or unaffected individuals. Results We discovered that subclade T1a1 was depleted in affectedBRCA2 mutation carriers compared with the rest of clade T (hazard ratio (HR) = 0.55; 95% confidence interval (CI), 0.34 to 0.88;P = 0.01). Compared with the most frequent haplogroup in the general population (that is, H and T clades), the T1a1 haplogroup has a HR of 0.62 (95% CI, 0.40 to 0.95;P = 0.03). We also identified three potential susceptibility loci, including G13708A/rs28359178, which has demonstrated an inverse association with familial breast cancer risk. Conclusions This study illustrates how original approaches such as the phylogeny-based method we used can empower classical molecular epidemiological studies aimed at identifying association or risk modification effects.